2010
DOI: 10.1177/000313481007600833
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic Leak Rate after Low Anterior Resection for Rectal Cancer after Chemoradiation Therapy

Abstract: Anastomotic leak may be the most concerning complication after colorectal anastomosis. To compare open with laparoscopic rectal resection, we must have accurate leak rates in patients who have received neoadjuvant chemoradiation therapy to serve as a benchmark for comparison. All patients who had preoperative chemoradiation therapy with rectal resection and low pelvic anastomosis for cancer in a single colorectal practice over a 7-year period were retrospectively reviewed. All patients had proximal diversion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Previous studies showed that the risk of anastomotic leakage, in anastomoses closer than 8 centimeters to the anal werge, in colorectal cancers may rise to 24% [3]. Therefore, temporary protective loop ileostomies have almost become a routine in surgeries to protect the anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed that the risk of anastomotic leakage, in anastomoses closer than 8 centimeters to the anal werge, in colorectal cancers may rise to 24% [3]. Therefore, temporary protective loop ileostomies have almost become a routine in surgeries to protect the anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Its treatment is based on tumor localisation, its stage, and spread; chemotherapy, radiotherapy and surgical treatments are related to each other [1,2]. The most fatal and frightening complication in rectal cancer surgery is anastomotic leakage [2,3]. In low-anterior and very low rectal cancers, the rate of anastomotic leakage is 3%-21% and the rate of mortality after leakage can be up to 22% [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… [6] , a multicentre randomized trial included 116 patients with 12 patients experiencing anastomotic leaks, while Phillips et al. [7] reported a 10.3% anastomotic leak rate but 8% clinical leak. Our case series has shown that we have an anastomotic leak of 6.5% (3/45) which is lower than what has been noted in previous trials.…”
Section: Discussionmentioning
confidence: 99%